The role of operations managers in translating management ideas and practices between firms. Issue 4 (12th March 2022) - Spring, Martin; Unterhitzenberger, Christine
Abstract: The operations improvement literature is found to focus on the adoption of relatively stable, monolithic external management ideas, neglecting the processes by which such ideas and associated practices are identified in source organizations and changed before and during adoption. The notion of translation is used to analyze the way SME managers assimilate practices observed in larger firms during a management development programme. A model of the micropractices of operations managers during translation is developed. The five micropractices are: navigating distance; identifying and categorizing ideas; interacting with peers; persevering based on reassurance; re-embedding practices. The findings point to the importance of understanding that managers, especially in SMEs, are active in selecting and adapting parts of systemic improvement approaches such as lean, rather than simply choosing and adopting them wholesale. They also underline the importance of peer networking in the translation process. Senior managers who want to adopt management ideas must take account of translation in their strategies. Policy-makers who advocate and evaluate the use of well-known management ideas must also be aware that translation may mean that many useful practices are adopted, even if the adopting firms no longer explicitly espouse the overarching management idea of which these practices are a part.